One-year results of 31 cases with Cervical MicroEndoscopic Laminectomy compared with Kurokawa laminoplasty - Tokunaga, Masako; Hyoudo, Hironori; Nakagawa, Tomowaki; Sato, Tetsuro; Hoshikawa, Ken; Takahashi, Eiji (Journal of Spine Research, 2022)
Introduction: CMEL (Cervical MicroEndoscopic Laminotomy) using a spinal endoscope has been reported as a surgical treatment for cervical myelopathy. In our department, we have introduced a modified version (CMEL) of laminectomy. This technique is minimally invasive, but the selective decompression and discectomy may worsen the outcome compared with conventional treatment.Objective: To compare the 1-year results of the CMEL variant and the Kurokawa method in our department, and to clarify the usefulness and problems of the CMEL variant.Methods: The CMEL variant is a method of complete resection of the lamina between the open intervertebral space. The subjects were 31 cases of CMEL variant and 39 cases of Kurokawa method. The study items were operative time, blood loss, complications, postoperative hospital stay, JOA score before and 1 year after surgery, JOACMEQ, and neck pain NRS.Results: There was no difference in mean operative time. Mean blood loss was lower in the CMEL variant. There was no difference in JOA score before and after surgery, and no difference in JOACMEQ except for cervical spine function before surgery. There was no difference in neck pain NRS both preoperatively and postoperatively.Conclusions: The CMEL variant is an excellent technique with postoperative results comparable to those of the Kurokawa method, and also allows early discharge from the hospital due to its minimally invasive nature.